On converse lability and its decline from Vedic to Epic Sanskrit: The verb juṣ- ‘to enjoy’ and ‘to please’ - Pooth, Roland A. (Yearbook of the Poznan Linguistic Meeting, 2021)
In the Early Vedic language, we encounter two different systems of active vs. middle voice and valency oppositions. The emergence of many thematic Vedic transitive active forms (e.g. īráya-ti ‘to raise sth. or so.’) is obviously innovative and secondary when compared to labile, and formally more archaic athematic active forms (e.g. íyar-ti iyár-ti ‘to rise, to raise sth. or so.’). On this basis, it has been claimed that the original voice distinction was mainly driven by agency (i.e., volition, control, responsibility and animacy), whereas the secondary voice opposition was driven by transitivity distinctions and direct and indirect reflexive middle semantics (Pooth 2012, 2014). In this article, another verb in question, namely the psych verb juṣ- ‘to enjoy, to please’, will be examined as a parallel case to further discuss the general developments in the Vedic verb system, which are part of the general decline of lability and the increase of verb forms specified for transitive vs. intransitive behavior within Vedic (Kulikov 2014, 2012, 2006). This article will show that the Sanskrit psych verb juṣ- ‘to enjoy’ and ‘to please’ exhibits converse lability in Early Vedic Sanskrit, whereas it does not behave like this in Epic Sanskrit. The syntactic and semantic behavior of forms of juṣ- in both periods of Sanskrit will thus be compared.